Caleb Henry Carlton papers - Carlton, Caleb Henry, 1836-1923.; Horner, Mabel Carlton
Correspondence, diaries, articles, military transcripts and papers, biographical and genealogical materials, financial records, maps, charts, and other papers pertaining to Carlton's service in the Union Army and following the Civil War in wars with various American Indians in western United States. Documents his participation during the Peninsular Campaign (1862) including battles at Harrison's Landing, Malvern Hill, Mechanicsville (Battle of Beaver Dam Creek), and Yorktown, Va.; his capture during the Battle of Chickamauga (1863) and his imprisonment at Libby Prison in Richmond, Va.; and his service in the Atlanta Campaign (1864) including battles at Jonesboro, Kennesaw Mountain, and Marietta, Ga. Also documents government relations and war with Apache, Cheyenne, Dakota, Ute, and other American Indians during Carlton's service at Fort Sidney, Neb.; Fort Fetterman, Fort Laramie, and Fort Washakie (Camp Augur), Wyo.; and Fort Sedgwick, Colo. Includes maps and charts of the U.S. Army posts as well as family correspondence and a biography of Carlton written by his daughter, Mabel Carlton Horner. Correspondents include Henry C. Cook, William T. Sherman, Thomas John Wood, and Matthew H. Wright.
U.S. Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cook, Henry C. -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Wood, Thomas John, -- 1823-1906 -- Correspondence; Wright, Matthew H. -- Correspondence; Carlton family -- Correspondence; Libby Prison; Apache Indians; Atlanta Campaign, 1864.; Beaver Dam Creek, Battle of, Va., 1862.; Cheyenne Indians; Chickamauga, Battle of, Ga., 1863.; Dakota Indians; Fortification -- Colorado; Fortification -- Nebraska; Fortification -- Wyoming; Indians of North America -- Government relations; Indians of North America -- Wars -- 1866-1895.; Kennesaw Mountain, Battle of, Ga., 1864.; Malvern Hill, Battle of, Va., 1862.; Military bases -- United States; Peninsular Campaign, 1862.; Ute Indians; Fort Fetterman (Wyo.); Fort Laramie (Wyo.); Fort Sedgwick (Colo.); Fort Sidney (Neb.); Fort Washakie (Wyo.); Georgia -- History -- Civil War, 1861-1865 -- Campaigns; Harrison's Landing, Va. -- History; Jonesboro (Ga.) -- History; Marietta (Ga.) -- History; Mechanicsville (Hanover County, Va.) -- History; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Richmond (Va.) -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; West (U.S.) -- History; Yorktown (Va.) -- History; Army officers